2008
DOI: 10.5454/mi.2.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacteria in Tempe Bitter Taste Formation: Microbiological and Molecular Biological Analysis Based on 16S rRNA Gene

Abstract: Tempe is traditional Indonesian food. It has a variety of tastes, sometimes with a hint of bitterness, which may differ in intensity. The cause of bitterness in tempe has never been reported previously. In this study, the aim is to identify whether bacteria play a role in the formation of bitter tastes in tempe. Sensory tests were carried out in order to determine the scores of bitter-taste-intensity in tempe. The sensory test on EMP, WJB, CLR, DRG, and MLB tempe shows that EMP tempe has the highest score (2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 16 publications
1
45
0
8
Order By: Relevance
“…were dominant bacteria found in EMP tempeh, while Klebsiella sp. and Pseudomonas putida were the dominant bacteria in WJB tempeh (Barus et al 2008). A study by Ayu et al (2014) showed that Klebsiella pneumoniae from Indonesian tempeh were genetically different from pathogenic isolates.…”
Section: Discussionmentioning
confidence: 99%
“…were dominant bacteria found in EMP tempeh, while Klebsiella sp. and Pseudomonas putida were the dominant bacteria in WJB tempeh (Barus et al 2008). A study by Ayu et al (2014) showed that Klebsiella pneumoniae from Indonesian tempeh were genetically different from pathogenic isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Other 12 contaminants such as Brevibacterium epidermidis and Micrococcus luteus known to play a role in the formation of antioxidants in tempeh (Klus and Barz 1995). Furthermore, bacteria in tempeh is also known as one of the factors that play a role in the formation of a bitter taste in tempeh (Barus et al 2008). A diverse array of lactid acid bacteria and yeasts also play important role in Indonesian tempeh production (Efriwati et al 2013).…”
mentioning
confidence: 99%
“…The process of tempeh making in Indonesia is still using conventional methods with uncontrolled condition (Barus et al 2008). During the fermentation process, not only fungi involved but also bacteria play important roles in the formation of flavor and nutrition.…”
mentioning
confidence: 99%
See 2 more Smart Citations